Characterization of Wastewater in Two U.S. Cattle Slaughterhouses. (1st September 2018) - Ziara, Rami M. M.; Li, Shaobin; Subbiah, Jeyamkondan; Dvorak, Bruce I.
Abstract : Recent changes related to antimicrobial intervention technologies and reduction in product loss have affected cattle slaughterhouse wastewater streams. In this study, wastewater samples were collected from two cattle slaughterhouses located in the Midwest of the United States, focusing on the overall wastewater, antimicrobial interventions, and viscera and offal processing. The wastewater concentrations were affected by the water use, dilution, processes, and wastewater pretreatment that occurs within the slaughterhouse. Even though there were differences in the wastewater concentrations, the overall wastewater loads for both slaughterhouses were similar. The overall mean total solids (TS), volatile solids (VS), 5‐day biological chemical demand (BOD5 ), and chemical oxygen demand (COD) wastewater loads for the two slaughterhouses were 16.8, 10.0, 4.7, and 12.5 kg/1000 kg live weight killed, respectively. Wastewater streams from antimicrobial interventions have low pH and are potential sources of shock loadings. Wastewater from viscera and offal processing has high nutrient concentration; therefore, any improvement in this process could enhance the sustainability the industry.